RETRACTED: Several Chaotic Analysis of Lorenz System - Alam, Md. Shakhawat; Ahmed, Payer (European Scientific Journal, ESJ, 2017)
This paper has been retracted on 27.11.2021. The reasons for the retraction are included in the retraction notice available on this website.